Mediações e recepções midiáticas da religião: movimento "Canção Nova" - Bertotto, Cláudio (2010)
This is a study about mediation and reception of media from Televison Canção Nova, a television channel linked to Catholic Charismatic Renewal. It had as one of its main goal to analyze the reasons which some people often watch this TV channel; it also aims to evaluate how the viewers absorb the ideology, messages, themes, and other subjects they watch and look into it from the receivers point of view, how the religious media experience happens in the individual. The mediation methodology allows answering about the television reception in building religious experiences. This work has been organized around the following steps: tracking the historical events that made possible the Pentecostal movements arise into Catholic Church; the connection between catholic movements and media, in special the television; and the understanding that, among several ways of experiencing religion, one of them might happen through television mediation. The research has based on media studies of reception, focusing on the methodology developed by Lopes, Borelli and Resende (2002) and the Martin-Barbero s theory of mediation. Having interviews as data of collection instruments and also, taking into account conceptually and theoretical the authors like Lipovetsky and Bauman, among others. The results suggest that the relationship between religious media and the receivers, currently, comes to be a tool to promote an individual religious experience with a great emotional appeal towards them